Comparison of Students Science Process Skills on Measurement Material Based on Gender - Bayu, Bayu; Rosdianto, Haris; Wijaya, Andika Kusuma; Teeka, Chat (Radiasi : Jurnal Berkala Pendidikan Fisika, 2025)
This study is a survey study conducted because of the different tendencies between male and female students. In addition, there has been no study that specifically examines each SPS indicator of male and female students with the aim of showing weaknesses and strengths between them based on the SPS indicators. Based on this statement, this study aims to describe and compare the profiles of basic science process skills of male and female students. This study uses tests as instruments and quota sampling techniques to select grade X students from State Senior High Schools in Singkawang. Data were analyzed using a combination of quantitative descriptive analysis and comparative statistical tests. The results of the study showed that overall, most of the basic science process skill indicators were in the 'moderate' category for both genders. However, the communication indicator stood out in the 'high' category. Female students had an advantage in basic science process skills compared to male students, although both genders showed the same weaknesses. On the other hand, male students were only superior to female students in the measurement indicator.